PERMAINAN TRADISIONAL MODIFIKASI SEBAGAI MEDIA PEMBELAJARAN BAGI ANAK USIA DINI - Kiryasyah, Purwa Yudha; Saputri, Lora Rahma; Fatimah, Anggita Suria; Sahrani, Syanindita Sifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The world of play is the world of children. Playing is a medium of stimulation for aspects of physical-motor, social-emotional, language, and cognitive development. Traditional games provide opportunities for children as a medium to bring out their potential for development. In traditional games, children will develop the ability to work together, interact with each other, and have the ability to obey rules. The purpose of modified traditional games is to introduce old games so that they are still interesting for children and children do it in a fun way. For the activities that have been carried out at Taman Kanak-Kanak Islam terpadu Fatmawati, located at Perum Mulya Mekar Indah, Desa Mulya Mekar, Kabupaten Purwakarta, Provinsi Jawa Barat totaling 15 children, consisting of 5 boys, 10 girls with an average age of 4-8 years. With many children involved in traditional games, it will develop children’s abilities to socialize and stimulate various aspects of development.